Using lifeworld philosophy in education to intertwine caring and learning: an illustration of ways of learning how to care. Issue 1 (2nd January 2019) - Hörberg, Ulrica; Galvin, Kathleen; Ekebergh, Margaretha; Ozolins, Lise-Lotte
ABSTRACT: Our general purpose is to show how a philosophically oriented theoretical foundation, drawn from a lifeworld perspective can serve as a coherent direction for caring practices in education. We argue that both caring and learning share the same ontological foundation and point to this intertwining from a philosophical perspective. We proceed by illustrating shared epistemological ground through some novel educational practices in the professional preparation of carers. Beginning in a phenomenologically oriented philosophical foundation, we will first unfold what this means in the practice of caring, and secondly what it means for education and learning to care in humanly sensitive ways. We then share some ways that may be valuable in supporting learning and health that provides a basis for an existential understanding. We argue that existential understanding may offer a way to bridge the categorisations in contemporary health care that flow from problematic dualisms such as mind and body, illness and well-being, theory and practice, caring and learning. Ways of overcoming such dualistic splits and new existential understandings are needed to pave the way for a care that is up to the task of responding to both human possibilities and vulnerabilities, within the complexity of existence. As such, we argue that caring and learning are to be understood as an intertwined phenomenon of pivotal importance in education of both sensible and sensitive carers. Lifeworld led didactics and reflection, which are seen as the core of learning, constitute an important educational strategy here.